Relative entropy method for measure solutions of the growth-fragmentation equation - Debiec, Tomasz; Doumic, Marie; Gwiazda, Piotr; Wiedemann, Emil (SIAM Journal on Mathematical Analysis, 2018)
The aim of this study is to generalize recent results of the two last authors on entropy methods for measure solutions of the renewal equation to other classes of structured population problems. Specifically, we develop a generalized relative entropy inequality for the growth-fragmentation equation and prove asymptotic convergence to a steady-state solution, even when the initial datum is only a nonnegative measure.
CRIS-Team Scopus Importer:2023-01-17
Keywords: Generalized young measure; Growth-fragmentation equation; Measure solutions; Relative entropy; Structured population